NATO–EU Enlargement Policy - Methoxha, Inida (Mediterranean Journal of Social Sciences, 2012)
NATO and EU are both significant part of the European Security Architecture. Within Europe, both NATO and the EU havesought to promote democratic standards in the defense and security sphere and have placed this among the criteria for accessioncandidates. Between these two Organizations has similarities but there are differences, which will be addressed more extensively in thispaper. The first part of this paper aims to present the criterias of enlargemet in both organization, the differences and contrasts in theprocess of NATO-EU enlargement, which have an overlap in terms of their membership; disparities and similarities that exist in theenlargement process according to the criteria for accession in both organization; challenges and prospects of further enlargements of EUand NATO. The other part of this paper will be focus on the consequences of NATO-EU enlargements on regional dimension.